Incidencia del Apoyo Familiar en el Proceso Educativo de los Estudiantes del Grado Quinto de una Institución Educativa De Riohacha. - Pinto Garcia, Dalianys Daleth; Rodero Barbosa, Danelis Paola (Universidad Antonio Nariño, 2022)
The integration of parents in the educational process of children is affected for various reasons, among which some parents lack interest in the institutional processes organized by some teachers, the above, can permeate the academic performance of minors, that is, Therefore, the present study aimed to describe the incidence of Family Support in the Educational Process of Fifth Grade Children of the Happy Kids Educational Institution in the Special, Tourist and Cultural District of Riohacha, for this, they established a methodology of type descriptive study with a qualitative approach, in which the Perception Survey prepared by Tobón (2018) was implemented as a measurement instrument and applied to 25 students belonging to the aforementioned degree and institution.